Public Expenditure and Financial Accountability Assessment : Federal Democratic Republic of Ethiopia (Somali Regional State Government) - World Bank (World Bank, Washington, DC, 2020)
The objective of the Public Expenditure and Financial Accountability (PEFA) assessment is to review the current performance of the public financial management (PFM) systems, processes, and institutions of the Somali regional government since the last assessment in 2015. The assessment is aimed at assisting the government in identifying PFM weaknesses that may inhibit effective delivery of services to its citizens and the realization of its development objectives in general. Furthermore, the findings of the PEFA assessment will assist the government in developing a PFM reform strategy and provide the basis for a coherent PFM reform program that can be supported by development partners (DPs), as well as through the government’s own initiatives. The Somali assessment covered regional government budgeted units, extra-budgetary units (EBUs), Office of the Regional Auditor General (ORAG), the regional council, public enterprises, and the chamber of commerce assessment shows the state of PFM performance of the region at the time of the fieldwork as of November 2019. The assessment management framework, oversight, and quality assurance are summarized in this report.